Optimization of Axial Vibration Attenuation of Periodic Structure with Nonlinear Stiffness without Addition of Mass - Vasconcellos, Diego P. [UNESP]; Silveira, Marcos [UNESP] (ASME International, 2020)
We explore the vibration attenuation of a periodic structure when one absorber with nonlinear cubic stiffness is included without increasing the total mass. Metastructures, and specifically periodic structures, present interesting characteristics for vibration attenuation that are not found in classical structures. These characteristics have been explored for automotive and aerospace applications, among others, as structures with low mass are paramount for these industries, and keeping low vibration levels in wide frequency range is also desirable. It has been shown that the addition of vibration absorbers in a periodic arrangement can provide vibration attenuation for shock input without increasing the total mass of a structure. In this work, the dynamical response of a metastructure with one nonlinear vibration absorber, with same mass as original structure, optimized for vibration attenuation under harmonic input is compared with a base metastructure without absorbers and a metastructure with linear absorbers via the evaluation of the H2 norm of the frequency response. A simplified approach is used to compare linear and nonlinear stiffness based on deformation energy, by considering linear and nonlinear restoring forces to be equal at mean deformation. The dynamical response of the optimal system is obtained numerically, and an optimization procedure based on sequential quadratic programming (SQP) is proposed to find the optimal position and stiffness coefficients of only one nonlinear absorber, showing that it results in lower level of vibrations than original structure and than structure with linear absorbers, while almost the same level as a structure with all nonlinear absorbers.
Keywords: Non-linear vibration; vibration isolation